The impacts of pragmatic knowledge on the effectiveness of oral communication: English teachers of Adama science and technology university in focus - Tujuba, Diriba Eticha; Woldemariam, Haileleul Zeleke (Green Publication, 2018)
The main purpose of this study was to explore the impacts of pragmatic knowledge on the effectiveness of oral communication. Both quantitative and qualitative methodology were employed in this study. The study was conducted in Adama Science and Technology University and the data were collected from 33 English language teachers. Purposive sampling was used to select the study sample. The data collection instruments used during the study were Multiple Choice Questionnaire, Discourse Completion Test, Interview and Communication Quiz. All the data collection instruments were developed after the necessary literature were reviewed. The data gathered through the Multiple Choices Questionnaire and Communication Quiz were analyzed based on percentages while the data collected through Discourse Completion Test and the Interviews were analyzed descriptively. The findings of the study revealed that, the majority of the English language teachers in Adama Science and Technology University have lower pragmatic competence. It was learned that the majority of the teachers have problems of communication. The collected data revealed that poor pragmatic competence has greatly affected the effectiveness of oral communication. Finally recommendations such as including pragmatics skills in language classes and giving short term training about application of pragmatics were forwarded based on the findings of the study.
* Ph.D. Scholar, Andhra University, College of Arts and Commerce, Department of English ** Associate Professor/Deputy Director, Department of Communication, Faculty of Human Sciences, Namibia University of Science and Technology, Windhoek, Namibia
Keywords: Pragmatic knowledge; Effectiveness of oral communication; English language teachers’ pragmatic competence